Comparison of synthetic hydroxyapatite and porous polyethylene implants in eviscerated rabbit eyes - Schellini, Silvana Artioli [UNESP]; Marques, MEA; Padovani, Carlos Roberto [UNESP]; Taga, E. M.; Rossa, R. (Lippincott Williams & Wilkins, 2003)
Purpose: Synthetic hydroxyapatite and porous polyethylene (Polipore) spheres were placed in rabbits' eviscerated cavities to evaluate tissue reaction and volume maintenance.Methods. Fifty-six Norfolk albino rabbits underwent unilateral evisceration and implantation of synthetic hydroxyapatite (H group, 28 animals) or porous polyethylene spheres (P group, 28 animals). Postoperative reactions, animal behavior, and socket conditions were monitored. Light microscopy and morphometric evaluation with statistical analysis of the exenterated orbits were performed at 7, 15, 30, 60, 90, 120, and 180 days. Scanning electron microscopy was appraised 7, 60, and 180 days after surgery.Results: Two animals from the H group and 1 from the P group had extrusion 7 days after surgery. Throughout the experimental period, the synthetic hydroxyapatite caused more inflammation than the porous polyethylene material. Ingrowth in the sphere occurred 7 to 15 days after the surgery in both groups, and the tissue reaction became denser at approximate to60 to 90 days, when bony metaplasia began in the H group. Volume maintenance was better in the P group and with a smaller pseudocapsule surrounding the implanted sphere than in the H group.Conclusions: Clinical findings demonstrated mild inflammation inside the sphere and in the pseudocapsule surrounding it and better cavity volume maintenance in the P group animals. The authors consider porous polyethylene a more suitable material than synthetic hydroxyapatite for use in anophthalmic cavity reconstruction.